1998
DOI: 10.1074/jbc.273.34.21875
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Cyclooxygenase-2 Transcription and Activity in Phorbol Ester-treated Human Mammary Epithelial Cells

Abstract: We determined whether resveratrol, a phenolic antioxidant found in grapes and other food products, inhibited phorbol ester (PMA)-mediated induction of COX-2 in human mammary and oral epithelial cells. Treatment of cells with PMA induces COX-2 and causes a marked increase in the production of prostaglandin E 2 . These effects were inhibited by resveratrol. Resveratrol suppressed PMA-mediated increases in COX-2 mRNA and protein. Nuclear run-offs revealed increased rates of COX-2 transcription after treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
446
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 713 publications
(472 citation statements)
references
References 37 publications
18
446
1
4
Order By: Relevance
“…Its effects were mediated at the level of COX-2, by suppression of COX-2 gene expression and direct inhibition of COX activity, without effects on either of the PGE 2 synthases (cPGES and mPGES). Similar findings have been reported in human mammary epithelial cells, in which resveratrol inhibited phorbol myristate acetate (PMA)-induced PGE 2 production by blocking transcription and COX enzyme function (32). Studies investigating resveratrol-mediated inhibition of COX in other cell types have demonstrated inhibition of peroxidase function, with no effect on COX enzyme activity (33,34).…”
Section: Discussionsupporting
confidence: 76%
“…Its effects were mediated at the level of COX-2, by suppression of COX-2 gene expression and direct inhibition of COX activity, without effects on either of the PGE 2 synthases (cPGES and mPGES). Similar findings have been reported in human mammary epithelial cells, in which resveratrol inhibited phorbol myristate acetate (PMA)-induced PGE 2 production by blocking transcription and COX enzyme function (32). Studies investigating resveratrol-mediated inhibition of COX in other cell types have demonstrated inhibition of peroxidase function, with no effect on COX enzyme activity (33,34).…”
Section: Discussionsupporting
confidence: 76%
“…A similar mechanism may be operated by PMA (Ghosh and Baltimore, 1990). Both TNF and fecapentaene-12 activate AP1 (Zeng-gang et al, 1996;Holloway et al, 1998), which is important in the induction of COX2 transcription by v-Src (Xie and Herschman, 1995) and PMA (Subbaramaiah et al, 1998). Since curcumin inhibits AP1 dependent transactivation (Huang et al, 1991), some of the inhibitory e ects of curcumin on COX2 gene induction by the tumour promoters may also be mediated by inhibition of AP-1 (Kelley et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that resveratrol, a natural phytoalexin found in high concentrations in grape skin, has strong anti-carcinogenetic effects in in vitro systems and animal models. 40,41 Multiple potential mechanisms involving initiation, promotion and progression have been identified. 42,43 Although our observations support an antineoplastic role of resveratrol as reported by Savouret et al, 44 grape intake even among the highest quartiles was very low.…”
Section: Discussionmentioning
confidence: 99%